Dynamique sédimentaire et taphonomie des abris-sous-roche et des porches de grotte en milieu périglaciaire - Pascal Bertran; Cédric Beauval; Stéphane Boulogne; Michel Brenet; Julia Chrzavzez; Émilie Claud; Sandrine Costamagno; Véronique Laroulandie; Arnaud Lenoble; Philippe Malaurent; Bertrand Masson; Jean-Baptiste Mallye; et al. (Les Nouvelles de l’Archéologie, 2009)
The Gavarnie project allows documentation of the sedimentary dynamics and taphonomic processes of rockshelter and cave entrances in a modern periglacial environment in the central Pyrenees. Thermal records in a small cave show that the regime is significantly milder in the cavity than outside, mainly because of soil insulation by a snowdrift in winter. Such conditions are unfavourable for permafrost development, but induce intense washing of the deposits during snowmelt. Measurements indicate also that the rock fragments undergo slow creep at the surface of the talus due to rock and ice falls. At lower altitude in the alpine belt, biological activity plays an important role on the dynamics of cave entrances. Development of humus horizons associated to solifluction under the grass cover is a good modern analogue for understanding of the genesis of organic-rich layers typically observed in Upper Palaeolithic sequences in southwest France.